MICROTOMOGRAFIA DE RAIOS X NA CARACTERIZAÇÃO MICROMORFOLÓGICA DE SOLO SUBMETIDO A DIFERENTES MANEJOS - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2013)
The X-ray computed microtomography (CT) represents a non-invasive technique that can be used with success to analyze physical properties by the soil scientists without destroying the structure of the soil. The technique has as advantage over conventional methods the characterization of the soil porous system in three dimensions, which allow morphological property analyses such as connectivity and tortuosity of the pores. However, as the soil is a non-homogeneous and complex system, the CT technique needs specific methodologies for digital image processing, mainly during the segmentation procedure. The objectives of this work were: 1) to develop a methodology for microtomographic digital image processing; 2) to characterize the soil structure by using micromorphology analysis of samples submitted to non-tillage and conventional systems collected in three distinct layers (0-10, 10-20 and 20-30 cm); and 3) to identify possible changes in the porous system of the soil analyzed due to the effect of different management systems. The use of the CT technique and the procedures adopted for microtomographic digital image processing show to be efficient for the micromorphologic characterization of soil porous system. Soil under non-tillage system presented the best results from the agricultural point of view regarding porosity, total number of pores, connectivity and tortuosity in comparison to the conventional tillage.
Keywords: estrutura do solo; análise de imagens; conectividade e tortuosidade; structure of soil; image analysis; connectivity and tortuosity; CNPQ::CIENCIAS EXATAS E DA TERRA::FISICA